Workshop: Implementing Positive Discipline for Leading Principals in Alor Regency - Credo Gregori Betty; Engelbertus Nggalu Bali; Angelikus Nama Koten; Sartika Kale; Theodorina Novyani Seran; Vanida Mundiarti; Frans K. Selly (Early Childhood Education Development and Studies (ECEDS), 2024)
The Sekolah Penggerak Program launched by the Ministry of Education and Culture of Indonesia aims to improve the quality of education by accelerating schools to become drivers of positive change. This program focuses on the development of students' literacy, numeracy, and character through training for principals and teachers. Its implementation is carried out through stages of preliminary studies, method identification, workshops, and evaluation. The main challenges in this program include teachers' lack of understanding of the Independent Curriculum and limited facilities. However, ongoing training and support from school leaders are crucial for the program's success. The results show an increase in the competence of teachers and principals in implementing the curriculum, which positively impacts the quality of education and student learning outcomes. This program is expected to be a catalyst for transforming the education system in Indonesia, creating an inclusive and high-quality educational ecosystem.